Rare renal proximal tubular dysfunctions in primary biliary cholangitis - Xiaoxiao Shi; Tianchen Guo; Yubing Wen; Wei Ye; Wenling Ye; Ke Zheng; Yan Qin; Xuemei Li; Fengchun Zhang; Limeng Chen (Renal Failure)
Introduction Renal involvement of primary biliary cholangitis (PBC) usually presents as distal renal tubular acidosis. Proximal tubular (PT) dysfunctions in PBC were rarely reported with unclear clinicopathological characteristics and renal prognosis.Methods We identified 11 cases of PBC with PT dysfunctions (PBC-PT). Their medical document, kidney pathology, and follow-up data were retrospectively reviewed and analyzed.Results The 11 PBC-PT patients were mainly middle-aged (57.8 ± 5.2 years) females (81.8%). Most of them were asymptomatic PBC (7, 63.6%) with a high prevalence of elevated serum immunoglobulin M (IgM, 81.8%) and G (IgG, 54.5%) levels. In the kidney, they had a mean estimated glomerular filtration rate (eGFR) level of 46.54 ± 23.03 ml/min/1.73m2, and 81.8% of them had eGFR below 60 ml/min/1.73m2. They showed different degrees of PT dysfunctions, including hyperuricosuria, hypouricemia, normoglycemic glycosuria, generalized aminoaciduria, hyperphosphaturia, and hypophosphatemia. Their kidney pathology showed tubulointerstitial nephritis with lymphoplasmacytic infiltrates, brush border defects, and proximal tubulitis. After glucocorticoids treatment, the PT dysfunctions manifesting as hypophosphatemia, hypouricemia, and renal glycosuria all recovered, and the eGFR levels were improved from 43.24 ± 19.60 ml/min/1.73m2 to 55.02 ± 21.14 ml/min/1.73m2 (p = 0.028), accompanied by significant improvements of serum IgM levels (from 5.97 ± 4.55 g/L to 2.09 ± 1.48 g/L, p = 0.019).Conclusions The PT dysfunctions were rare in PBC patients, and glucocorticoids treatment could benefit the improvements of eGFR and tubular functions.